If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 64 = 82 + -1m Reorder the terms: 64 + 5m = 82 + -1m Solving 64 + 5m = 82 + -1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'm' to each side of the equation. 64 + 5m + m = 82 + -1m + m Combine like terms: 5m + m = 6m 64 + 6m = 82 + -1m + m Combine like terms: -1m + m = 0 64 + 6m = 82 + 0 64 + 6m = 82 Add '-64' to each side of the equation. 64 + -64 + 6m = 82 + -64 Combine like terms: 64 + -64 = 0 0 + 6m = 82 + -64 6m = 82 + -64 Combine like terms: 82 + -64 = 18 6m = 18 Divide each side by '6'. m = 3 Simplifying m = 3
| 6-8x-5x+6= | | 3(1+7x)+5x=159 | | [s-6]=2 | | x^2+x-1296=0 | | (10sinx)/(7x) | | 4/3x3.14r^3 | | 3x-20=2x-40 | | 2x+20=62 | | 8y+5=3y-9 | | -3/4y=24.5 | | M=3x^2+5x-4 | | 6v^3-v^2-6v+1= | | 5x-(3-9x)=13x+20 | | 4x-0.4=2.8 | | dy/dx=4y | | 59.7(59.7)+x=63.9(63.9) | | 10+19p=80 | | 2c+d=7d+2 | | 4x^2+103=3 | | 4x^2-15x+12=8x+9 | | 5(f-9)=-65 | | 7.3Y-518=51.9 | | -10(s+1)=-44 | | 8x-(6x-9)+(3x-2)=4-7x-8 | | h(t)=-4.9t^2+4.9t+294 | | -5(n+8)= | | [(-21)+(-6)]+12= | | 5(3-2x)=5(x-2) | | x^2+12+61=0 | | 13m+4n-6m+8n= | | -10(x+6)= | | 1.42+1.67x=2+1.38x |